2008
DOI: 10.1007/s12017-007-8021-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Factors in Autonomic Nervous System Plasticity and Dysfunction

Abstract: During development, neurotrophic factors are known to play important roles in regulating the survival of neurons in the autonomic nervous system (ANS) and the formation of their synaptic connectivity with their peripheral targets in the cardiovascular, digestive, and other organ systems. Emerging findings suggest that neurotrophic factors may also affect the functionality of the ANS during adult life and may, in part, mediate the effects of environmental factors such as exercise and dietary energy intake on AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 162 publications
(143 reference statements)
0
20
0
Order By: Relevance
“…Nerve cells in the brain are remarkably responsive to exercise. Studies of animal models and of human subjects support the hypothesis that exercise induces the expression of neurotrophic factors which, in turn, promote structural and functional plasticity of neurons and their resistance to injury and disease (Gomez-Pinilla, 2008; Mattson and Wan, 2008; Zoladz and Pilc, 2010). BDNF has been the most intensively studied exercise-induced neurotrophic factor.…”
Section: Neurotrophic Factors Mediate Anti-aging Effects Of Endurancementioning
confidence: 94%
“…Nerve cells in the brain are remarkably responsive to exercise. Studies of animal models and of human subjects support the hypothesis that exercise induces the expression of neurotrophic factors which, in turn, promote structural and functional plasticity of neurons and their resistance to injury and disease (Gomez-Pinilla, 2008; Mattson and Wan, 2008; Zoladz and Pilc, 2010). BDNF has been the most intensively studied exercise-induced neurotrophic factor.…”
Section: Neurotrophic Factors Mediate Anti-aging Effects Of Endurancementioning
confidence: 94%
“…BDNF is known to play an important role in regulating the survival of neurons in the autonomic nervous system and the formation of their synaptic connectivity with their peripheral targets in the cardiovascular, digestive, and other organ systems. Emerging evidence suggests that BDNF may also affect the function of the autonomic nervous system during adult life and may, in part, mediate the effects of environmental factors, such as exercise and dietary energy intake, on autonomic nervous system neurons and target cells [53]. BDNF has also been shown to be a modulator of visceral sensory transmission, suggesting that BDNF is involved in maturation and/or plasticity in the arterial baroreceptor pathway [54].…”
Section: Mir-132 Has Functions In the Cardiovascular Systemmentioning
confidence: 99%
“…Neurotrophic factors play a crucial role in regulating neurons in the ANS, and in the formation of synaptic connections with peripheral targets in the cardiovascular, digestive, and other organ systems during development. They also influence the function of the ANS in adults ( 11 ). Neurotrophic factors, including brain-derived neurotrophic factor (BDNF), nerve growth factor, insulin-like growth factor (IGF), and ciliary neurotrophic factor may regulate ANS functions ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…They also influence the function of the ANS in adults ( 11 ). Neurotrophic factors, including brain-derived neurotrophic factor (BDNF), nerve growth factor, insulin-like growth factor (IGF), and ciliary neurotrophic factor may regulate ANS functions ( 11 ). Recent studies have found that BDNF and IGF-1 can modify the functions of the central nervous system (CNS) that are involved in neurological and psychiatric diseases, including epilepsy ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%